1996
DOI: 10.1002/(sici)1520-6300(1996)8:4<457::aid-ajhb5>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Age at menarche in Peruvian girls at sea level and at high altitude: Effect of ethnic background and socioeconomic status

Abstract: The objective of the present study was to determine median age at menarche using the status quo method and the independent effects of ethnic background and socioeconomic status on the age at menarche in Peruvian girls from two distinct levels at altitude: Lima (150 m) and Cerro de Pasco (4,340 m). The sample included 503 girls from Lima and 625 girls from Cerro de Pasco, ages 10–18 years. Ethnic background was determined by four parental surnames. Subjects were classified as Quechua when one or more surnames w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
2
12
0
1
Order By: Relevance
“…Other factors such as nutrition (Simodon et al, 1997), seasonality (Boldsen, 1992), physical activity (Malina, 1983), and altitude (Gonzales et al, 1996) also have shown a significant effect on age at menarche. In a recent review of published studies on the variability of age at menarche throughout the world, Thomas et al (2001) found that the factors that best explained the variation in age at menarche were adult illiteracy rate and vegetable caloric consumption.…”
supporting
confidence: 84%
“…Other factors such as nutrition (Simodon et al, 1997), seasonality (Boldsen, 1992), physical activity (Malina, 1983), and altitude (Gonzales et al, 1996) also have shown a significant effect on age at menarche. In a recent review of published studies on the variability of age at menarche throughout the world, Thomas et al (2001) found that the factors that best explained the variation in age at menarche were adult illiteracy rate and vegetable caloric consumption.…”
supporting
confidence: 84%
“…Only subjects who had not yet reached sexual maturation (boys) or menarche (girls) were enrolled into the study. Sexual maturation is delayed in this population, as has been observed for other high-altitude populations in the region (Gonzales et al, 1996;Greksa, 1990).…”
Section: Subjectssupporting
confidence: 77%
“…This could be related to the delayed presentation of adrenarche and delayed onset of puberty observed in girls living at high altitude compared with those living at sea level (Góñez et al 1993, Gonzales et al 1996. Early age at adrenopause could also be related to the early onset of menopause observed at high altitude (Gonzales & Villena 1997).…”
Section: Discussionmentioning
confidence: 99%